Roman-alphabeted Greek and transliteration in the digital language practices of Greek secondary school pupils on Facebook. Issue 1 (1st April 2017) - Lees, Christopher; Politis, Periklis; Koutsogiannis, Dimitris
This article highlights the uses of Roman-alphabeted Greek as observed in the language practices of fifteen Greek secondary school pupils on their Facebook profiles. We argue that far from the use of Latin alphabet posing a threat to the Greek language, as it is often described, Roman-alphabeted Greek merely forms part of teenagers' digital communication exchanges. Furthermore, our data point to a clear preference for using the Greek script as opposed to the Latin. In many instances where the Latin alphabet is used, pupils, albeit with gender-related differences, use orthographic transliteration, so as to adhere to standard Greek spelling. At the same time, we draw attention to an emerging trend in alphabet choice, where other languages are transcribed using the Greek script.